Determination and Validation of Nitrate Levels of Vegetables Grown in the Mediterranean Region - Fatma Hepsağ (Turkish Journal of Agriculture: Food Science and Technology)
In our study, validation was carried out at 24 and 200 mg/kg enrichment for residue analysis of nitrate active substance only in lettuce samples. Analyses were performed by using high performance liquid chromatography (HPLC) in lettuce, spinach, salad and arugula samples. In order to eliminate the matrix effect, matrix calibration was used, ie calibration of lettuce samples. Validation of the method was performed with criteria such as precision, repeatability, repeatability limit, reproducibility, repeatability limit, accuracy, linearity of calibration and recovery. The calibration curve was found as linear in the range of 0.2-40 mg/kg. The recovery from the samples is between 97.3-100.2 %. The repeatability and reproducibility values for the two concentrations were 1.89 (matrix+24 ppm) and 3.65 (matrix+200 ppm), 3.951 (matrix+24 ppm) and 3.456 (matrix+200 ppm), respectively. The repeatability and reproducibility limit values are within acceptable limits. Accuracy, precision, combined uncertainty and extended uncertainty (95% confidence: k=2) were found as 0.015 (matrix+24 ppm) and 0.004 (matrix+200 ppm), 0.039 (matrix+24 ppm) and 0.006 (matrix+200 ppm), 0.041 (matrix+24 ppm) and 0.007 (matrix+200 ppm), 0.082 (matrix+24 ppm) and 0.014 (matrix+200 ppm). In our study, the highest nitrate ratio was determined in spinach with 3486 mg/kg in total 102 samples. Lettuce following spinach (2825 mg/kg) showed lower nitrate content, while lower concentrations of nitrate were detected in iceberg (1985 mg/kg) and arugula (1870 mg/kg), respectively. The results may be useful in estimating body intake levels for research on the effects of nitrite and nitrate on human health in vegetable producers and in our daily diet. In addition, the nitrate content of the vegetables analysed in the study is an indicator of the use of nitrogenous fertilizers in the Mediterranean region, but showed no problem for human and animal health.